Effect of Wilhelmy Plate Material on Hysteresis of Langmuir Film Isotherms - Sudheesh, Siji; Ahmad, Jamil (Asian Journal of Chemistry, 2013)
Langmuir isotherms and their hysteresis for monolayers of octadecanoic acid, octadecylamine and octadecanethiol were measured at 25 ºC using an automated Langmuir trough. Surface pressures were measured with Wilhelmy plates made of platinum plate, filter paper and microscope slide cover made of glass. Hysteresis curves for octadecylamine on Pt plate and glass indicate that after the first compression, the contact angle increases. During subsequent cycles, the contact angle remains constant. For the Wilhelmy plate made of filter paper, the hysteresis curves are reversible for all the three substances, showing that the contact angle remains constant during all the cycles. For octadecanoic acid and octadecanethiol, adsorption on both Pt and glass is comparatively small, since subsequent isotherms differ only slightly from the first.